Acute effect of add‐on therapy with tofogliflozin, a sodium glucose co‐transporter 2 inhibitor, on 24‐hours glucose profile and glycaemic variability evaluated by continuous glucose monitoring in patients with type 2 diabetes receiving dipeptidyl peptidase‐4 inhibitors. Issue 11 (19th August 2021) - Iijima, Toshie; Hosonuma, Soichiro; Kurai, Hidetaka; Kajitani, Hayato; Sakurai, Shintaro; Tomaru, Takuya; Jojima, Teruo; Usui, Isao; Aso, Yoshimasa
Abstract: Aim: To investigate acute effects of add‐on therapy with the sodium glucose co‐transporter 2 inhibitor tofogliflozin to dipeptidyl peptidase (DPP)‐4 inhibitors on 24‐hours glucose profile and glycaemic variability evaluated by continuous glucose monitoring (CGM) in patients with type 2 diabetes. Patients and Methods: We studied 17 patients with type 2 diabetes who were hospitalised for glycaemic control. CGM was performed for 7 consecutive days in the last week of hospitalization. Tofogliflozin 20 mg/d was started on day 4 after initiating CGM and was administered to 10 patients receiving DPP‐4 inhibitors and 7 patients not receiving DPP‐4 inhibitors. We compared several CGM parameters between day 2‐3 (ie, before treatment with tofogliflozin) and day 5‐6 (ie, after starting treatment with tofogliflozin). Results: After starting treatment with tofogliflozin, mean 24‐hours glucose and postprandial glucose after each meal were significantly decreased in both groups of patients. Time in range (ie, at a glucose level of 70‐180 mg/dL) was significantly increased in both groups. The standard deviation of 24‐hours glucose and mean amplitude of glycaemic excursions (MAGE), 2 indexes of glycaemic variability, were significantly decreased in patients receiving DPP‐4 inhibitors but were unchanged in those not receiving these drugs. Conclusions: Add‐on therapy with tofogliflozin to DPP‐4 inhibitors acutely reduces 24‐hours glucose levels and improves glycaemic variability in patients with type 2 diabetes.